The effect of manipulating grapevine vigour and canopy microclimate on yield, grape composition and wine quality - Smart, Richard E.(Richard Ernest) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (D. Sc. Agric.) -- University of Stellenbosch, 1995.